The Relationship between ESG Practices and Banking Performance in Indonesia - Haryono; Elok Heniwati; Syarif M Helmi (APSSAI, 2025)
Research aims: This study examines the impact of environmental, social, and governance (ESG) factors on the financial performance of banks in the Indonesian banking sector. The analysis explores the relationship between 25 ESG pillar dimensions and bank performance indicators from 2019 to 2023. Design/Methodology/Approach: A 129 data observation from 42 Indonesian banks was analyzed using three regression models to assess the influence of ESG initiatives on financial indicators. ESG dimensions, measured as dummy variables based on annual report disclosures, serve as independent variables, while performance indicators, measured using accounting and market variables, serve as dependent variables. Research findings: The findings indicate that environmental factors do not have a significant impact on bank performance, while social and governance factors show a positive and significant influence. These results suggest that Indonesian banks focusing on social and governance initiatives are likely to achieve better financial outcomes. Theoretical contribution/Originality: The study offers practitioners and academics a set of empirically validated ESG predictors relevant to bank performance.